O naruszaniu podstawowych zasad postępowania naukowego. “Wzgórze przeznaczenia archeologii” górą skandalu - Kolb, Frank; Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2014)
The article discusses ethical aspects and thoroughness of scientific research on the example of German excavations in Troy, conducted in 1988 by a team from Tübingen University. The author demonstrates how archaeologists became entangled in various relationships with polictical and economic circles, which subsequently yielded an interpretation of findings which ensured financial and media support. The text is an emphatic call for independence and objectivity of scientific investigations that should remain free of any pressure. Although the paper relies on an example from the milieu of archaeologists. historians and classical philologists, the appeal of the authors is a universal one.